2015
DOI: 10.1002/anie.201505974
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy to Control the Reactivation of Frustrated Lewis Pairs from Shelf‐Stable Carbene Borane Complexes

Abstract: N-Phosphine oxide substituted imidazolylidenes (PoxIms) have been synthesized and fully characterized. These species can undergo significant changes to the spatial environment surrounding their carbene center through rotation of the phosphine oxide moiety. Either classical Lewis adducts (CLAs) or frustrated Lewis pairs (FLPs) are thus formed with B(C6F5)3 depending on the orientation of the phosphine oxide group. A strategy to reactivate FLPs from CLAs by exploiting molecular motions that are responsive to ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 54 publications
1
46
0
Order By: Relevance
“…This enlarged surface area was ascribed to the random displacement of 2D PAF-6 layers increasing the gas contact space to some extent. [32,33] The NL-DFT pore size distribution www.advancedsciencenews.com www.advancedscience.com of NanoPAF-6 centers at 1.2 and 4.2 nm ( Figure S7b, Supporting Information). The emergence of 4.2 nm mesoporosity compared with PAF-6 (1.2 nm) is attributed to gaps in the accumulated PAF nanosheets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enlarged surface area was ascribed to the random displacement of 2D PAF-6 layers increasing the gas contact space to some extent. [32,33] The NL-DFT pore size distribution www.advancedsciencenews.com www.advancedscience.com of NanoPAF-6 centers at 1.2 and 4.2 nm ( Figure S7b, Supporting Information). The emergence of 4.2 nm mesoporosity compared with PAF-6 (1.2 nm) is attributed to gaps in the accumulated PAF nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] This high activity is on account of two reasons: 1) the aromatic network enriches the phenyl molecule (1,1-diphenylethylene) via -interaction and the concentrated substrates accelerate the metal-free hydrogenation reaction (Table S2, Supporting Information); [32,33] 2) the accumulated PAF nanosheets provide the confined space surrounding their N Triazine centers to restrict the rearrangement and escape of BCF molecules which enhances the chemical durability of LP groups in NanoPAF-6@BCF. [4,5,32,33] The hydrogenation of unsaturated bonds has received wide interest because of the immense number of opportunities that exist to prepare high-value products. [53] Because NanoPAF-6@BCF catalyst shows remarkable reactivity toward the activation of the H 2 molecule, various imine compounds were chosen to investigate its catalysis capability for other hydrogenation reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, PoxIms contain the N ‐phosphine oxide moiety, which can work as a Lewis base and an electrophile, and a nucleophilic/Lewis basic carbene, which should allow multipurpose utility (vide infra). A simplified synthetic scheme to PoxIms is shown in Figure . The isolable and shelf‐stable precursors PoxIm ⋅ HOTf ( 2 ) were obtained from the reaction of imidazoles ( 1 ) and t Bu 2 PCl, followed by oxidation with H 2 O 2 .…”
Section: Nhcs Equipped With Phosphine Oxide Substituentsmentioning
confidence: 99%
“…[4] There are few experimental demonstrations that both the carbene and the additional substituent(s) in the multifunctional NHCs are strategically used in amultipurpose fashion (Figure 1). [5,6] Beyond satisfying the natural curiosity of the research chemist, multifunctional multipurpose NHCs shouldc ontribute to the further development of especially organic and organometallicc hemistry,s incet hese carbenes are potentially crucial parts of unprecedented molecular transformationsa sw ell as novel organoand metal-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…4 We have developed N-phosphine oxide-substituted imidazolylidenes (PoxIms) as a novel class of isolable, multifunctional NHCs and demonstrated their multifunctionality. 5 During previous studies, we have revealed that the complexation between PoxIms and Lewis acids such as B(C 6 F 5 ) 3 or a cationic Pd complex occurs either by coordination through the carbene and/ or the phosphoryl group ( Figure 1). For example, the reaction between PoxIms and B(C 6 F 5 ) 3 showed two types of complexation that furnished the phosphorylborane and the carbene borane adducts at ¹90 and 25°C, respectively, which led us to develop a frustration revival system using their external-stimuli responsive reactivity (Figure 1a, b).…”
mentioning
confidence: 97%